Analysis on voltage stability on power grid connected to solar PV - Kamaruddin M.I.; Kamil K.; Hashim H.; Chong K.H.; Mansor M.H. (American Institute of Physics, 2025)
Electricity is essential to human being and is a key factor in a country's economic growth. Researchers have been urged to concentrate on improving power supply, efficiency and reliability as a result of electricity issues. This pursuit has increased the desire to integrate renewable energy which in terms of solar photovoltaic (PV) into the power grid in order to address the issue of energy scarcity. However, the significant rise in solar power generations and decreasing the power production of synchronous generators in the grid also may present technological complications and major impacts on system stability. Voltage stability refers to the power system network's ability to sustain fixed tolerable voltage across all network buses under standard operating conditions as well as after a disruption. This research focuses on the impact of solar PV energy as a source of network disruption. This is due to the fact that this type of energy source has now advanced to a higher level of integration into the national grid. Furthermore, Voltage Stability Indices (VSI) were being introduced to indicates the voltage stability of the system. Under VSI there were several voltage stability indicators can be used to determine the weakest area and voltage stability of the system. To achieve the main research objectives, the network system is developed based on the test case of the IEEE 30-bus system by using Power System Simulator for Engineering software (PSSE). Voltage stability indicators such as the Fast Voltage Stability Index (FVSI) and Line Stability Factor (LQP) were proposed in this project. FVSI is used to identify the weakest area of the system, while LQP is used to analyse the voltage stability of the system. Last but not least the impact of solar PV on line loading percentage is also being observed. The reason for this is that if there is a higher output of solar PV integrated into the system, it may affect the system's line loading percentage. The simulation results will be elucidated based on the results obtained to strengthen the theory behind the related works. ? 2024 Author(s).